Online sensing of palladium in flowing streams. Issue 4 (19th December 2016) - Bu, Xiaodong; Williams, Michael; Jo, Junyong; Koide, Kazunori; Welch, Christopher J.
Abstract : Rapid palladium (Pd) catalyzed deallylation of an uncoloured reagent within a flowing stream affords a dose dependent colour formation that can be used for convenient online analysis of trace levels of Pd using a modified HPLC instrument. Abstract : Rapid palladium (Pd) catalyzed deallylation of an uncoloured reagent within a flowing stream affords a dose dependent colour formation that can be used for convenient online analysis of trace levels of Pd contamination using a modified HPLC instrument. An application to the online sensing of Pd breakthrough from a flow through Pd adsorption cartridge is described. An alternative configuration of the instrumentation allows the rapid (<1 min) and accurate measurement of Pd levels within samples injected via a conventional HPLC autosampler.